Effect of Fluid Shear Stress on Portal Vein Remodeling in a Rat Model of Portal Hypertension - Bin Wen; Jian Liang; Xin Deng; Ran Chen; Peichun Peng (Gastroenterology Research and Practice)
Aims. To explore the effects and mechanisms of fluid shear stress on portal vein remodeling in a rat model of portal hypertension. Methods. Subcutaneous injections of CCl4 were given to establish a rat model of liver cirrhosis and portal hypertension. Biomechanical technology was adopted to determine the dynamic changes of haemodynamic indices and fluid shear stress. Nitric oxide (NO), synthase (NOS), and endothelin-1 (ET-1) of the portal vein blood were measured. Changes in geometric structure and ultrastructure of the portal vein were observed using optical and electron microscopy. Results. After the CC14 injections, rat haemodynamics were notably altered. From week 4 onwards, PVP, PVF, and PVR gradually and significantly increased (P<0.05 versus baseline). The fluid shear stress declined from week 4 onwards (P<0.01 versus control group). NO, NOS, and ET-1 increased after repeated CCI4 injections. Hematoxylin and eosin staining showed thickened portal vein walls, with increased inside and outside diameters. Electron microscopy revealed different degrees of endothelial cell degeneration, destruction of basement membrane integrity, proliferating, and hypertrophic smooth muscle cells. Conclusions. Fluid shear stress not only influenced the biomechanical environment of the portal vein but also participated in vascular remodeling.